Re-imagining Olympus: Keats and the Mythology of the Individual Consciousness - Sheley, Erin (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractBy the time John Keats began to write his great mythological works, the use of the classical world in poetry had become somewhat scorned in English literary circles, after the allegorical excesses of the eighteenth century. In Keats’ imagination, however, the Greco-Roman pantheon served not as a source of aesthetic embellishment but as part of a new, organic mythology of his own creation. For Keats, the self-exploration of a personal consciousness most closely approximates divinity, and such divinity depends upon interaction with the immediate, earthly space surrounding an individual. In this essay I explore Keats’ use of myth to access this personal identity, which he does frequently through three poetic techniques. The first I call “mythological sense,” meaning the apprehension of mythological allusions acting as a sixth sense for the narrator as he perceives his surroundings. The second is the physical boundedness that constricts mythological poems. The third is his use of embodied figures, initially anonymous mythological forms which appear first as objects in the narrator’s sensual experience, their mythological identifications secondary and often revealed only after their physical significance has been explored.